‘Florida Beauty’ Strawberry - Vance M. Whitaker; Natalia A. Peres; Shinsuke Agehara (EDIS)
‘Florida Beauty’ (PPAF) is a new strawberry cultivar released by the University of Florida and commercialized in 2017. This cultivar was originally evaluated as breeding selection FL 12.121-5. ‘Florida Beauty’ originated from a 2012 cross between Queensland Australia selection 2010-119 (female parent) and ‘Florida Radiance’ (male parent). It has been tested over several years in field plots at the University of Florida Gulf Coast Research and Education Center (GCREC) in Wimauma, FL, at the Florida Strawberry Growers Association (FSGA) headquarters in Dover, FL, and on several commercial farms. Data from these trials have been used to generate the following information and recommendations to help growers obtain optimum performance of this cultivar in west-central Florida. Comparisons are made to the current industry standard cultivars ‘Florida Radiance’ (Chandler et al. 2009) and Sweet Sensation® ‘Florida127’ (Whitaker et al. 2015) (hereafter referred to as ‘Florida127’).